Development and performance evaluation of an environment and health friendly water pumping system - SINHA, PANKAJ; SINHA, JITENDRA (Journal of Soil and Water Conservation, 2021)
An experiment was conducted on development and performance evaluation of an environment and health friendly water pumping system. The aim of the work was to efficiently utilize the human energy for lifting and moving the water through the some improvisation in a common gym cycle. The wheel of the gym cycle was opened and a V belt has been inserted at the periphery and the other end was fixed in the pulley of a centrifugal pump without any electrical fittings. After conversion around 1600 RPM was achieved at pump pulley with 50 pedalling per minute. The performance of this improvised water pumping system was evaluated at the different suction lift, different discharge head and at carrying different horizontal distances. It was found very useful for exercising as well as lifting harvested water to irrigate small field. The results showed that the variations in discharge with different discharge head and different horizontal pipe distance were more significant as compared to the variation in the suction lifts. The discharge of 0.58 lps (35 lpm) was obtained at 3.58m of suction, 0.27m of discharge head and 10 m horizontal distance which was enough to provide water for small field, open gymnasium, hostels etc. The system can work for a maximum suction lift of 3.58m in normal pedaling condition. It can be seen that the discharge is varying from 0.30 lps to 0.64 lps under different conditions. Based on the result obtained it is concluded that common gym cycle can be improvised to work as human pedal powered water lifting device.